The quest for multi-functional medicines: path for progress: the SERM story - Jordan, V. Craig (Henry Stewart Talks, 2011)
Selected Estrogen Receptor Modulators (SERMs) are a group of medicines that switch on and switch off estrogen target sites around a post-menopausal woman's body. They are anti-estrogenic and block estrogen activated breast cancer growth and increase bone density and lower cholesterol, which are estrogenic properties. Raloxifene is a pioneering SERM used to prevent and treat osteoporosis and is approved in the United States of America to reduce the risk of breast cancer in post-menopausal women.
Reviewed at 2018/01/17